Respuesta :

Answer:

the function is odd

Step-by-step explanation:

A function f(x) is said to be even if f(-x) = f(x)

On the other hand, f(x) is said to be odd if f(-x)≠ f(x).

We plug in -x in place of x in the given function and simplify;

f(-x) = 3(-x-1)^4

f(-x) = 3[-1(x+1)]^4

f(-x) = 3 *(-1)^4 * (x+1)^4

f(-x) = 3(x+1)^4 ≠ f(x)

Therefore, the function given is odd

Answer:

The given function is odd

Step-by-step explanation:

we need to determine the function [tex]f(x)=3(x-1)^{4}[/tex] is odd or even

Since, A function f(x) is said to be even if [tex]f(-x) = f(x)[/tex]

and f(x) is said to be odd if [tex]f(-x)= - f(x)[/tex] and [tex]f(-x) \neq f(x)[/tex]

We Replace x with -x in the given function and solve;

[tex]f(x)=3(x-1)^{4}[/tex]

[tex]f(-x)=3(-x-1)^{4}[/tex]

take out the negative common,

[tex]f(-x)=3[-(x+1)]^{4}[/tex]

Since [tex](-1)^{4}=1[/tex]

[tex]f(-x)=3(x+1)^{4}[/tex]

[tex]f(-x) \neq f(x)[/tex]

Hence, the given function is odd